Pengaruh Peran Komite Audit, Umur Perusahaan dan Ukuran Perusahaan terhadap Audit Delay: Studi pada Perusahaan Sub Sektor Property dan Real Estate yang Listing di Bursa Efek Indonesia 2018-2021 - Ghassani Malahati; Efrizal Syofyan (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to find out the effect of audit committee, company age and size firm on audit delay in property and real estate sub-sector companies listed on the Indonesia Stock Exchange in 2018-2021. This research is a quantitative research. The samples collected was 188 data based of the purposive sampling technique. The data used are secondary data obtained from 1 or company websites and other sites related to this research. The research data were analyzed using multiple linear regression analysis. Based on statistical analysis, it can be concluded that audit committee and firm age do not have a negative effect on audit delay. Company size has a negative effect on audit delay.